2020
DOI: 10.1111/1749-4877.12444
|View full text |Cite
|
Sign up to set email alerts
|

A first comparison of bone histomorphometry in extant domestic horses (Equus caballus) and a Pleistocene Indian wild horse (Equus namadicus)

Abstract: The microstructural features of the tissue of long bones subjected to different biomechanical stresses could be a helpful tool for a better understanding of locomotor behavior in extant and extinct mammals, including equids. However, few researches have attempted to describe the bone tissue of extinct horses. In our study, we analyze and compare the histomorphometric features of the bone tissue in extant modern horses, Equus caballus, and Equus namadicus, a Pleistocene Indian extinct wild horse. The number, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
2
12
0
2
Order By: Relevance
“…In all samples, it was noted that the relative density of secondary osteons varies according to the location, registering areas with higher concentrations (even with the development of Haversian tissue) and areas where they were scarce and scattered. The remodeling pattern observed in each type of skeletal element is, in general lines, similar to that described in other works for limb bones of both extant (e.g., [ 18 , 25 , 56 59 ]) and extinct (e.g., [ 18 , 26 , 27 , 55 , 57 , 61 ]) equids.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In all samples, it was noted that the relative density of secondary osteons varies according to the location, registering areas with higher concentrations (even with the development of Haversian tissue) and areas where they were scarce and scattered. The remodeling pattern observed in each type of skeletal element is, in general lines, similar to that described in other works for limb bones of both extant (e.g., [ 18 , 25 , 56 59 ]) and extinct (e.g., [ 18 , 26 , 27 , 55 , 57 , 61 ]) equids.…”
Section: Discussionsupporting
confidence: 87%
“…Observations performed in this study reflected that all skeletal elements are fundamentally characterized by the presence of fibrolamellar bone tissue, although with differences in the vascular pattern, coinciding, in general terms, with the descriptions of other equids, both extant [ 18 , 25 , 55 – 60 ] and extinct [ 18 , 26 28 , 57 , 61 , 62 ]. The overall presence of this type of tissue suggests that this species has, during early stages of the growth, a relatively fast rate of bone deposition.…”
Section: Discussionsupporting
confidence: 64%
“…These inferences of extinct taxa rely on our understanding of the histology of extant species (e.g., Köhler et al, 2012), which has shown that key life history traits like birth, growth rate, age at maturity, and age at death are recorded in the bone microstructure (Amprino, 1947; Chinsamy et al, 1995; de Margerie et al, 2002; Castanet et al, 2004; Chinsamy and Valenzuela, 2008; Erismis and Chinsamy, 2010; Marín-Moratalla et al, 2013; Kolb et al, 2015b; Jordana et al, 2016; Nacarino-Meneses et al, 2016a; Montoya-Sanhueza and Chinsamy, 2017; Nacarino-Meneses and Köhler, 2018). In extinct mammals, palaeohistological investigations have focussed on bones of extinct rodents (Geiger et al, 2013; Kolb et al, 2015b; Orlandi-Oliveras et al, 2016; Garrone et al, 2019; Miszkiewicz et al, 2019, 2020), lagomorphs (Kolb et al, 2015b; Moncunill-Solé et al, 2016), hedgehogs (Kolb et al, 2015b), wombats (Walker et al, 2020), hippos (Kolb et al, 2015b), seals (Woolley et al, 2019), bovids (Köhler and Moyà-Solà, 2009; Marín-Moratalla et al, 2011), cervids (Amson et al, 2015; Kolb et al, 2015a; Lyras et al, 2016, 2019), ursids (Veitschegger et al, 2018), and equids (Sander and Andrássy, 2006; Martínez-Maza et al, 2014; Orlandi-Oliveras et al, 2018; Nacarino-Meneses and Orlandi-Oliveras, 2019; Zedda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another morphological feature that suggests a greater capability of the bovine osteons to resist mechanical stress is their higher eccentricity than sheep. In other species, a higher value of eccentricity has been described in those animals with remarkable locomotor skills, such as horse, goat, moufflon, wild boar, rabbit (Locke 2004;Zedda et al 2008Zedda et al , 2017Zedda et al , 2019Zedda et al , 2020 and man (Goldman et al 2005;Pfeiffer et al 2006). Negative allometry in osteon size has also been described by Felder et al (2017) taking into consideration humeri and femora of 56 mammal species and by Barak et al (2013) in trabecular bone of mice, rats and man.…”
Section: Discussionmentioning
confidence: 97%
“…The size of osteons and Haversian canals is related to the amount of biomechanical stress affecting bones, while it is possible to take information on locomotor behavior, not only in extant but also in extinct mammals (Pfeiffer et al 2006;Nacarino-Meneses et al 2016;Zedda et al 2020). Higher Haversian canals occur in animals with greater mobility, associated with the need to improve blood supply (Owerkowicz and Crompton 1995).…”
Section: Introductionmentioning
confidence: 99%